Mind-Wandering Mediates the Associations Between Neuroticism and Conscientiousness, and Tendencies Towards Smartphone Use Disorder - Müller, Marko; Sindermann, Cornelia; Rozgonjuk, Dmitri; Montag, Christian (Frontiers in Psychology, 2021)
Mounting evidence suggests that smartphone overuse / Smartphone Use Disorder (SmUD) is associated with negative emotionality accompanying overuse of the smartphone to productivity loss due to constant interruptions. Given the large number of smartphone users around the globe (currently about 3.5 billion) and the fact that many individuals carry around their smartphone 24/7, it is of high importance to better understand the phenomenon of smartphone overuse. One theory, initially built to explain specific Internet Use Disorders including mobile forms, guiding research in the area of smartphone overuse, is the Interaction of Person-Affect-Cognition and Execution (I-PACE) model. The present study focuses on P variables of the I-PACE model and more specifically, the personality traits neuroticism and conscientiousness, which represent two robust vulnerability factors linked to SmUD according to a recent meta-analysis. Beyond that, we tested also process variables of the I-PACE model, namely mind-wandering and fear of missing out (FoMO), which could be seen as mediators between individual differences in personality and tendencies towards SmUD. The effective sample comprised 414 study participants (151 men and 263 women, age M = 33.6, SD = 13.5). By applying a structural equation modelling (SEM) technique, we observed that the association of high neuroticism and low conscientiousness with higher levels of SmUD were mediated by higher scores in mind-wandering. These novel findings can help to understand the association between personality and SmUD in more detail.